Privacy and security issues in data mining and machine learning International ECML/PKDD workshop, PSDML 2010, Barcelona, Spain, September 24, 2010 : revised selected papers - PSDML 2010 (2010 Barcelona, Spain); Dimitrakakis, Christos; SpringerLink (Online service). (aBerlin, Heidelberg Springer, 2011)
aThis book constitutes the refereed proceedings of the International ECML/PKDD Workshop on Privacy and Security Issues in Data Mining and Machine Learning, PSDML 2010, held in Barcelona, Spain, in September 2010. The 11 revised full papers presented were carefully reviewed and selected from 21 submissions. The papers range from data privacy to security applications, focusing on detecting malicious behavior in computer systems.
Electronic reproduction.
Keywords: Data mining -- Security measures -- Congresses; Machine learning -- Congresses; Electronic books